Acetone gas sensors based on ZnO nanostructures decorated with Pt and Nb - Wongrat E. (2017)
© 2017 Elsevier Ltd and Techna Group S.r.l. In this study, the highly selective acetone gas sensors based on ZnO nanostructures with sputtered Pt and Nb were presented. The ZnO nanostructures were systematically prepared onto alumina substrates by a thermal oxidation technique at a working temperature of 500 °C. Pt and Nb were then coated on the prepared ZnO nanostructures by a DC pulse sputtering technique. Their surface morphologies and chemical compositions were analyzed via field emission scanning electron microscopy (FE-SEM), energy dispersive spectroscopy (EDS), transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS). The ZnO nanostructures exhibited the wire-like structures while the ZnO nanostructures with Pt and Nb decoration (ZnO:Pt and ZnO:Nb) showed the fine particles attaching onto their surfaces. The gas sensing characteristics were evaluated toward acetone, ethanol and ethylene vapor at the operating temperatures of 275–450 °C. The maximum sensor response of sensors based on ZnO:Pt and ZnO:Nb were found upon exposure toward acetone vapor at 1000 ppm concentration with the value of 188.0 and 224.0, respectively. The observed sensor response enhancement in ZnO:Pt sensor is clearly explained by the catalytic effect in the oxygen and acetone adsorption reaction, while the sensor response enhancement in ZnO:Nb sensor is clarified by an adjustment of the depletion layer width to larger at the n-n nanoheterojunction of two semiconductors (ZnO:Nb 2 O 5 ) leading to the sensor response enhancement with a higher resistance in air.